Face aux pollutions : hiérarchies et solidarités entre fumeuses de poissons à Abidjan - Marie Belland; Alain Bonnassieux (VertigO)
In West Africa, women who smoke fish and meat face high environmental risks because their activity exposes them to high concentrations of harmful air emissions. Through a case study of women workers at a smoking site adjacent to a popular market in Abidjan, this paper describes the perceptions of air pollution, its health effects, and the individual and collective strategies and practices of women smokers to reduce it. Particular emphasis is placed on the working relationships between smokers and the helpers they employ, since these hierarchies influence their level of exposure to pollution. In this perspective, relations of dependence structuring women-led activities of the popular economy are analyzed, and especially the practices of entrusting the juvenile workforce, as well as the professional path of young helpers in the face of risks, between exploitation and emancipation. This article proposes to consider together environmental degradations, occupational health risks, economic opportunities for working-class women, and reciprocal social obligations among female smokers in the Ivorian capital.